Rapid Constructions of Microstructures for Optical Fiber Sensors Using a Commercial CO2 Laser System - Irawan, Rudi (Bentham Open, 2008)
Exposing an optical fiber core to the measurand surrounding the fiber is often used to enhance the sensitivity of an optical fiber sensor. This paper reports on the rapid fabrication of microstructures in an optical fiber using a CO(2) laser system which help exposing the optical fiber core to the measurand. The direct-write CO(2) laser system used is originally designed for engraving the polymeric material. Fabrications of microstructures such as in-fiber microhole, D-shaped fiber, in-fiber microchannel, side-sliced fiber and tapered fiber were attempted. The microstructures in the fibers were examined using a SEM and an optical microscope. Quality of microstructures shown by the SEM images and promising results from fluorescence sensor tests using in-fiber microchannels of 100μm width, 210μm depth and 10mm length show the prospect of this method for use in optical fiber sensor development. The direct-write CO(2) laser system is a flexible and fast machining tool for fabricating microstructures in an optical fiber, and can possibly be a replacement of the time consuming chemical etching and polishing methods used for microstructure fabrications of optical the fiber sensors reported in other literatures.